2011
DOI: 10.1007/s00408-011-9303-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cognitive Function After a Three-Month Pulmonary Rehabilitation Program for COPD Patients

Abstract: The objective of the study was to evaluate the effect of multidisciplinary pulmonary rehabilitation program on cognitive function in COPD patients, adjusting for potential confounders (gender, age, tobacco consumption, and educational level). In this prospective study, 34 COPD patients were submitted to neuropsychological testing before and after a 3-month pulmonary rehabilitation program. A control group with 18 healthy subjects of similar age, sex, and educational status was used to compare the cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 28 publications
1
50
0
2
Order By: Relevance
“…97 The mechanisms behind cognitive dysfunction probably vary with each of these associations; some studies have demonstrated that participation in rehabilitation programs and the use of supplementary oxygen in patients with hypoxemia may decrease the risk of cognitive abnormalities. 94,98 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…97 The mechanisms behind cognitive dysfunction probably vary with each of these associations; some studies have demonstrated that participation in rehabilitation programs and the use of supplementary oxygen in patients with hypoxemia may decrease the risk of cognitive abnormalities. 94,98 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…Pulmonary rehabilitation (PR) is a well established gold standard of care for COPD patients, which improves patients' dyspnoea, QoL and exercise tolerance [11,12]. Recent studies have also shown that cognitive function [13], depression and anxiety [14,15] may improve with PR. One meta-analysis demonstrated significant improvement in the fatigue subscale of a QoL questionnaire after PR [16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cardiac rehabilitation in HF patients has been shown to confer long-term improvements in attention/executive function and memory and such gains were suggested to involve increases in physical fitness [40]. Pulmonary rehabilitation has also been linked with cognitive benefits in multiple domains in patients with COPD [41]. Prospective studies are strongly encouraged to determine the most effective behavioral and medical interventions that may be able to reduce risk for poor neurocognitive outcomes in HF patients with and without COPD.…”
Section: Discussionmentioning
confidence: 99%